1993
DOI: 10.1056/nejm199309093291103
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of Treatment with Filgrastim for Relapse of Leukemia and Myelodysplasia after Allogeneic Bone Marrow Transplantation

Abstract: Filgrastim may be effective in selected cases of leukemic relapse after allogeneic bone marrow transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(42 citation statements)
references
References 17 publications
0
42
0
Order By: Relevance
“…[32][33][34] None of the trials published up to now, have shown an increased relapse rate in patients treated with G-CSF post-transplantation. 4,[9][10][11][12][13][14][15]33,34 This is in line with our data and we observed relapse in three of 22 patients receiving rhG-CSF and in seven of 25 patients without rhG-CSF.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] None of the trials published up to now, have shown an increased relapse rate in patients treated with G-CSF post-transplantation. 4,[9][10][11][12][13][14][15]33,34 This is in line with our data and we observed relapse in three of 22 patients receiving rhG-CSF and in seven of 25 patients without rhG-CSF.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11]13 Our results raise the possibility that this heterogeneity in response may be explained on the basis of relative G-CSFR isoform expression. Leukemic cells which proliferate but fail to terminally differentiate in response to G-CSF may express abnormally high levels or fail to down-regulate the expression of the differentiation-defective class IV isoform, while the leukemic cells of patients who respond to G-CSF by entering into remission may express and regulate levels of the class IV isoform similar to normal myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies with G-CSF explored its potential as a treatment for acute myelogenous leukemia (AML), with hopes that it would drive leukemic myeloid cells to terminally differentiate. 5 While a few cases of G-CSF-induced remission of AML have been described, [6][7][8] in the overwhelming majority of cases of AML, G-CSF-induced maturation is either incomplete or absent, while the proliferative response of these cells to G-CSF persists. 5,[8][9][10][11][12][13] The basis for this aberrant maturational response of leukemic myeloid cells to G-CSF is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…All died of disease progression, 126, 29 and 37 days after relapse, respectively. Patient 25 received only G-CSF for disease control 16 and failed to respond. Subsequent treatment was limited to intermittent steroids for an idiopathic thrombocytopenic purpura (ITP)-like syndrome.…”
Section: Cytogenetic Patterns At Relapsementioning
confidence: 99%